1999
DOI: 10.1149/1.1392646
|View full text |Cite
|
Sign up to set email alerts
|

Li / β ‐  VOPO 4: A New 4 V System for Lithium Batteries

Abstract: Lithium intercalation into ␤-VOPO 4 has been performed, both chemically and electrochemically, with X-ray diffraction characterization of the resulting phases at various levels of intercalation-deintercalation. It is shown that intercalation occurs through a first-order transition at 3.98 V vs. Li ϩ /Li 0 , which leads to a ␤-LiVOPO 4 -like structure but with lithium ordering which doubles the a and b unit cell parameters. Starting from chemically intercalated ␤-Li 0.92 VOPO 4 , the reversible process involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
85
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 11 publications
(14 reference statements)
8
85
1
1
Order By: Relevance
“…Both the magnitudes and relative orientation of the quadrupole and chemical shift tensors can be determined from the analysis of the complete manifolds of ssbs. 1 -3 Vanadyl phosphates, VOPO 4 , present open 2D or 3D frameworks that are suitable for lithium intercalation processes and are good candidates for new cathode materials in lithium ion rechargeable batteries. Recently, the electrochemical behavior of the different phases of VOPO 4 has been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the magnitudes and relative orientation of the quadrupole and chemical shift tensors can be determined from the analysis of the complete manifolds of ssbs. 1 -3 Vanadyl phosphates, VOPO 4 , present open 2D or 3D frameworks that are suitable for lithium intercalation processes and are good candidates for new cathode materials in lithium ion rechargeable batteries. Recently, the electrochemical behavior of the different phases of VOPO 4 has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…1 -3 Vanadyl phosphates, VOPO 4 , present open 2D or 3D frameworks that are suitable for lithium intercalation processes and are good candidates for new cathode materials in lithium ion rechargeable batteries. Recently, the electrochemical behavior of the different phases of VOPO 4 has been investigated. 4 -7 These studies confirmed that VOPO 4 is promising as a cathode material with an electrochemical potential close to 4 V and a theoretical specific capacity of 165 mA h g 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, these materials were also investigated in the field of lithium battery research [13][14][15][16][17][18][19]. Up to now, seven polymorphs of this compound have been described:  I [20],  II [20,21],  [22],  [1,23],  [1],  [24,25], and  [26,27].…”
Section: Introductionmentioning
confidence: 99%